Electromagnetic flow of casson nanofluid over a vertical riga plate with ramped wall conditions - Khan, Hameed; Ali, Farhad; Khan, Naveed; Khan, Ilyas; Mohamed, Abdullah (Frontiers in Physics, 2022)
The present study aims to investigate the Casson nanofluids flow theoretically over a vertical Riga plate. The temperature and concentration with ramped and isothermal wall conditions are considered. Moreover, the fluid is considered electrically conducted. Concrete is considered as a base fluid while clay nanoparticles are added to it. The present flow regime is formulated in terms of a system of partial differential equations. Using dimensionless variables, the system of equations with the imposed boundary conditions is non-dimensionalized. The Laplace transform technique is used to calculate the exact solutions for the temperature, concentration, and velocity distributions. The effect of various embedded parameters on the velocity, temperature, and concentration fields are shown graphically and discussed physically. The variation in the skin friction for various values of clay nanoparticles volume fraction is shown in Table 1. The results indicate that adding 4% clay nanoparticles, enhanced the skin friction up to 9.08% in instance of ramped wall temperature (RWT) and 11.52% in isothermal wall temperature (IWT). This result is worth noting because the increase in skin friction causes rapid compaction of the cementitious materials and improves the tensile strength of the concrete.